Community pharmacy-based research in Spain (1995-2005): A bibliometric study (Pharmacy Practice, 2007)
Only one study evaluated the scientific activity in community pharmacies in Spain, and it was restricted to articles published in just two journals.Objective: To assess the scientific activity in community pharmacies in Spain through a bibliometric analysis of the original papers published during the years 1995-2005.Methods: IPA, MEDLINE, CSIC database and the journals Seguimiento Farmacoterapéutico y Pharmaceutical Care España were used as data sources. Production indicators, consumption indicators and the impact factor (IF) as a repercussion index were analyzed.Results: 122 articles were included in the review. The articles were published in 12 journals, 78.7% of them in Pharmaceutical Care España and Seguimiento Farmacoterapéutico. The mean number of authors per article was 4.2 (SD=2.1). The transitivity index was 71.3%. The total number of references cited in the articles was 2110. The mean number of references per article was 17.3 SD=9.3. The value of the insularity index was 57.6%. Self citation was 6.8% and the Price index was 66.5%. No impact factor was available for 6 journals.Conclusions: Publication of articles on community pharmacy-based research in Spain has undergone an important increase in the last 5 years. The existence of authors who publish very few studies, the high insularity index and the lack of randomized, controlled trials may be considered as negative indicators in community pharmacy-based research in Spain.